Effect of casting flow defects on the crack propagation in UHPFRC thin slabs by means of stereovision Digital Image Correlation. (30th December 2016) - Baril, M.A.; Sorelli, L.; Réthoré, J.; Baby, F.; Toutlemonde, F.; Ferrara, L.; Bernardi, S.; Fafard, M.
Graphical abstract: Abstract: Owing to their outstanding compressive strength and considerable cracking resistance, Ultra High Performance Fibre Reinforced Concrete (UHPFRC) have been recently successfully applied to thin bi-dimensional elements, e.g., plate and shells. As a critical aspect of UHPFRC technology, is work aims at experimentally investigating the effect of fibre orientation on the damage behaviour of UHPFRC 2-way thin slabs by means of stereovision digital image analysis. To this aim, the fibre orientation was perturbed by introducing a simple divider line as a temporary barrier to the casting flow of fresh concrete. The casting flow defect affected the fibre distribution by creating a weakened plane with a strong discontinuity. By varying the line direction and the position of the concentrated load position, six different slab configurations were fabricated and tested under punching load with hyperstatic boundary conditions. Then, the 3-D deformation field was measured by means of stereovision-based Digital Image Correlation (DIC). The results showed the critical importance of the fibre distribution on the microcracking growth and the structural ductility. The casting flow defect had a major impact on the observed microcrack pattern and growth especially before the peak load. When the defect crossed the loading point, the microcracks did not fully develop with an important reduction of the load-carrying capacity and the structural ductility. Finally, a simplified application of yield line theory allowed estimating the effect on the fibre distribution of the casting flow defects.